Analisis komparatif keuntungan budidaya rumput laut (gracilaria verrucosa) menggunakan metode sebar dan metode gantung pada tambak di Desa Lakawali pantai Kecamatan Malili Kabupaten Luwu Timur Provinsi Sulawesi Selatan - Vian, Ade; Yusuf, Sarini; Ruslaini (Jurnal Sosial Ekonomi Perikanan, 2021)
Demand for agar producing seaweed G. verrucosa continues to increase in both domestic and global markets. Currently, the seaweed farmers in Lakawali Pantai Village, Malili District, East Luwu Regency, South Sulawesi Province use the spread and the hanging method for seaweed culture in brackish ponds, but the profit of these method if applied in the same area of pond is unknown. Therefore, this study aims to determine the comparison of profit obtained by seaweed farmers using the spreading and the hanging method in the same area of pond. This research was conducted from February to March 2020. The sample selection in this study used a purposive sampling method where 10 respondents were chosen out of 35 seaweed farmers using the spread method and since only 1 farmer using the hanging method, this farmer was selected as respondent. The rearing time for seaweed in both cultivation methods was 30 days and this was calculated as one production cycle. Data obtained through observation, interviews and documentation and analyzed using the total cost analysis formula consisting of fixed, variable costs, revenues and profits. The t test was used to compare the profits of the two methods of seaweed cultivation. The results showed that the average profit of seaweed cultivation using the spread method was IDR. 3,076,548 / cycle / Ha and the hanging method was 9,046,651 / cycle / Ha. The studyindicated that the hanging method of seaweed cultivation was more profitable than the spreading method, therefore, it was recommended that farmerschange their seaweed culture prcaticeto hanging method in order to increase profits of the seaweed farm.